Decisions of the World Court relevant to the UN Convention on the Law of the Sea a reference guide - Kwiatkowska, Barbara (Kluwer Law International, 2002)
The entries cover principally judgments and orders (including the related pleadings) of the PCIJ and the ICJ and those decisions of Arbitral Tribunals and other third-party fora as well as national courts which have been relied upon in the Court's jurisprudence.